Strategies and motives for resistance to persuasion: an integrative framework - Fransen, Marieke L.; Smit, Edith G.; Verlegh, Peeter W. J. (Frontiers in Psychology, 2015)
Persuasion is an important element of human communication. But in many situations, we resist rather than embrace persuasive attempts. Resistance to persuasion has been studied in many different disciplines, including communication science, psychology and marketing. The present paper reviews and connects these diverse literatures, and provides an organizing framework for understanding and studying resistance. Four clusters of resistance strategies are defined (avoidance, contesting, biased processing, and empowerment), and these clusters are related to different motivations for resisting persuasion (threat to freedom, reluctance to change, and concerns of deception). We propose that, while avoidance strategies may be triggered by any of these motivations, contesting strategies are linked primarily to concerns of deception, while empowerment and biased processing strategies are most common when people are reluctant to change.